2000
DOI: 10.1083/jcb.148.5.957
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Tyrosine Residues 31 and 118 on Paxillin Regulates Cell Migration through an Association with Crk in Nbt-II Cells

Abstract: Identification of signaling molecules that regulate cell migration is important for understanding fundamental processes in development and the origin of various pathological conditions. The migration of Nara Bladder Tumor II (NBT-II) cells was used to determine which signaling molecules are specifically involved in the collagen-mediated locomotion. We show here that paxillin is tyrosine phosphorylated after induction of motility on collagen. Overexpression of paxillin mutants in which tyrosine 31 and/or tyrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
297
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(312 citation statements)
references
References 79 publications
13
297
1
1
Order By: Relevance
“…The initial assembly of integrin-associated focal adhesions requires FAK autophosphorylation on Tyr 397 and complex formation with Src. The FAK-Src signalling complex functions to recruit and phosphorylate various FAK-associated proteins including paxillin (Bellis et al, 1995;Schaller et al, 1995) which participates in the coordination of integrin-mediated cell motility (Klemke et al, 1998;Petit et al, 2000). We show here that FRNK and siRNA against FAK inhibited Tyr 397 phosphorylation of FAK and Tyr 118 phosphorylation of paxillin in HNSCC-derived cells, which is accompanied by decreased cell motility.…”
Section: Discussionmentioning
confidence: 74%
“…The initial assembly of integrin-associated focal adhesions requires FAK autophosphorylation on Tyr 397 and complex formation with Src. The FAK-Src signalling complex functions to recruit and phosphorylate various FAK-associated proteins including paxillin (Bellis et al, 1995;Schaller et al, 1995) which participates in the coordination of integrin-mediated cell motility (Klemke et al, 1998;Petit et al, 2000). We show here that FRNK and siRNA against FAK inhibited Tyr 397 phosphorylation of FAK and Tyr 118 phosphorylation of paxillin in HNSCC-derived cells, which is accompanied by decreased cell motility.…”
Section: Discussionmentioning
confidence: 74%
“…In response to motility signals, paxillin undergoes tyrosine phosphorylation primarily at two sites, Tyr-31/ 118 (Nakamura et al, 2000;Petit et al, 2000), and Src kinase has been implicated in regulating tyrosine phosphorylation of paxillin (Thomas et al, 1995;Richardson et al, 1997). As TIMP-2 suppresses cell migration (Ahn et al, 2004;Oh et al, 2004) and we showed in this study that TIMP-2 signaling downregulates Src kinase activity (Figure 1b), the effects of TIMP-2 on paxillin phosphorylation was examined.…”
mentioning
confidence: 71%
“…Our previous work in human Caco-2 intestinal epithelial cells, a cell line which progressively differentiates as it grows past confluence and is thus a widely used human intestinal epithelial cell in vitro model system, suggests that Crk binding to Srcphosphorylated p130 Cas is an important regulator of intestinal epithelial cell spreading and sheet migration on collagen IV (Sanders and Basson, 2005), one of the major components of the intestinal epithelial basement membrane in vivo. This work also suggests that Crk binding to paxillin, which plays an important role in regulating migration in some cell systems (Petit et al, 2000;Lamorte et al, 2003), is not as important for regulation of these processes in Caco-2 cells on collagen IV.…”
Section: Introductionmentioning
confidence: 80%